The Agriculture, food and health challenge : critical issues, perspectives and options - Francis, Diana (IICA Port of SpainTT, 2009)
Looks at issues relating to nutrition and health, the potential for greater food and fuel security from agriculture and the need to place greater emphasis on water-based food production systems, particularly given the influence of climate change on rising sea levels.